The impact of chitosan on seafood quality and human health: A review - Inanli, Ayse Gurel; Tumerkan, Elif T. Aksun; El Abed, Nariman; Regenstein, Joe M.; Ozogul, Fatih (Elsevier Science London, 2020)
Background: Seafood is highly susceptible to spoilage due to microbiological, chemical and enzymatic reactions, which are the principal causes of their quality deterioration. Therefore, greater consumer demand for high quality seafood along with a concern for the safety of the artificial preservatives currently used to prevent quality losses creates a challenge. Natural preservatives, such as chitosan biopolymer, are potential alternatives to maintain seafood quality by reducing microbial growth, increasing oxidative stability and protecting sensorial properties. Scope and approach: This review focuses on the use of chitosan as a food preservative, and its functional properties in food, such as antioxidant and antimicrobial activities, its importance as a dietary fibre and its use for enzymes-immobilization. The applications of this biopolymer on seafood and seafood products as a functional biomaterial and its health benefits are discussed. Key finding and conclusions: Chitosan is a functional biomaterial for the preservation of foods, mainly due to its natural origin and its excellent biological properties. It has antimicrobial activities against spoilage microorganisms and food-borne pathogens, and a strong antioxidant activity that can protect against lipid oxidation in seafood. Chitosan can also be characterized by its wide range of benefits for health promotion and disease prevention.
Keywords: Seafood; Fish; Chitosan; Food preservation